FROM FRAGRANCE / MEMORY VALUES TO BREATHİNG… RAİSHER FLOWERİNG / “PİNHAN” OF ELİF ŞAFAK - Arslan, Fatih; İşler, İlker (Salim DURUKOĞLU, 2020)
Fragrance is transported, it is the structure that carries and transports. Besides the unity of the senses, he has never lost his predecessor attitude. All the fragrances are transformed into identity by training through categories. All movable values are positive, negative, naive, disgusting, etc. passes to lower values such as. The essence of the smell evokes many different structures. The fragrance almost accepts the terms of the brain and heart and values itself. Physiological, psychological, social activities are around the scent. Acceptance of the nose is also acceptance of connotations. It is unthinkable that literature, which is more or less in the same places, does not benefit from this upper sensibility. Many texts in Turkish Literature invited the scent in a certain form and proportion to the geography coveted by the smell of the page. In the text of Elif Şafak, the smell is the marker that activates feminine sensors. The projections of character, place, time, and life are largely defined by the guidance of the scent. The first text, which is almost irrevocable, is the first novel in this narrative. "Pinhan" lived all the knotty, sincere structures of being the first with a maturity that was unlike any other principle. The scent of the fragrance accompanies the double sensations of "Pinhan". Thus, the fragrance goes beyond being a sensation and steps into the breath of speech. Smelling the novel is as much as reading.

Koku taşınır, taşıyan ve taşınan yapıdır. Duyuların olanca birlikteliği yanında öncül tavrını hiç kaybetmemiştir. Onca koku kendince kategorilerden geçerek, eğitilerek kimliğe dönüşür. Taşınır bütün değerler olumlu, olumsuz, naif, tiksinç vb. gibi alt değerlere geçer. Kokunun özüt oluşu da apayrı pek çok yapıyı çağrıştırır. Koku, adeta beynin ve kalbin hükümlerini kabullenir ve kendince bir değer biçer. Fizyolojik, psikolojik, sosyal pek çok eyleyen kokunun etrafındadır. Burnun kabulü çağrışımların da kabulüdür. Aşağı yukarı aynı yerlerde olan edebiyatın da bu üst duyumsallıktan faydalanmaması düşünülemez. Türk Edebiyatı’nda pek çok metin belli biçim ve orantıda kokuyu, sayfanın kokusuyla imrenilen coğrafyaya davet etmiştir. Elif Şafak metinlerinde ise koku feminen duyargaları harekete geçiren belirteçtir. Karakter, mekân, zaman, hayat izdüşümleri kokunun rehberliğinde tanımlanır büyük ölçüde. Hemen her anlatısında karşılaşılan bu durumun hazırlayıcısı bir daha dönülemez olan ilk metin, ilk romandır. “Pinhan” ilk olmanın bütün çetrefilli, samimi yapılarını hiç de ilke benzemeyen bir olgunlukla yaşamıştır. Kokunun arafı “Pinhan”ın çifte duyumlarına eşlik eder. Böylece koku duyum olmanın ötesine geçerek söz nefesine adım atar. Romanı koklamak okumak kadar olur.
KOKU/BELLEK DEĞERLERDEN SÖZ NEFESİNE… RAYİHA ÇİÇEKLENMESİ ve “PİNHAN”…
Keywords: Creative Arts and Writing; Sanat ve Edebiyat